2017
DOI: 10.1007/s10549-017-4322-5
|View full text |Cite
|
Sign up to set email alerts
|

Unenhanced magnetic resonance screening using fused diffusion-weighted imaging and maximum-intensity projection in patients with a personal history of breast cancer: role of fused DWI for postoperative screening

Abstract: An unenhanced AP had a short acquisition time of 5 min, and DWI MIPs showed NPVs greater than 99% across readers. The diagnostic performance of complete AP was equivalent to that of CP for screening patients with PHBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
1
11

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 35 publications
1
31
1
11
Order By: Relevance
“…29,30 However, there are some recent concerns about nephrogenic systemic fibrosis and gadolinium deposition in neural tissues, which provoked the search for noncontrast-enhanced breast MRI protocols. [1][2][3][4][5][6][7]31,32 The results of those and our present study show that DWI is highly effective in the detection and characterization of breast tumors, and it may be potentially used as an abbreviated MRI for screening or even for some diagnostic purposes. In this use, there might be no need to obtain additional sequences for detection and morphologic evaluation of breast tumors.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…29,30 However, there are some recent concerns about nephrogenic systemic fibrosis and gadolinium deposition in neural tissues, which provoked the search for noncontrast-enhanced breast MRI protocols. [1][2][3][4][5][6][7]31,32 The results of those and our present study show that DWI is highly effective in the detection and characterization of breast tumors, and it may be potentially used as an abbreviated MRI for screening or even for some diagnostic purposes. In this use, there might be no need to obtain additional sequences for detection and morphologic evaluation of breast tumors.…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, abbreviated breast MRI protocols have gained significant popularity due to their shorter acquisition time, lower cost, and comparable diagnostic accuracy to DCE‐MRI . However, there are some recent concerns about nephrogenic systemic fibrosis and gadolinium deposition in neural tissues, which provoked the search for noncontrast‐enhanced breast MRI protocols . The results of those and our present study show that DWI is highly effective in the detection and characterization of breast tumors, and it may be potentially used as an abbreviated MRI for screening or even for some diagnostic purposes.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, gadolinium remains in the patient's body, including the brain, and the long‐term effects are still not understood, so the repetitive use of gadolinium‐based contrast agents would be minimized. Thus, the potential role of non‐enhanced MRI for breast cancer patients has been proposed in several studies with the use of combination of DWI and other sequences …”
mentioning
confidence: 99%
“…DWI signal intensity reflects the restriction of the free motion of water molecules in the body and provides indirect information about cellularity and microstructure . Several studies have demonstrated its potential role in detecting breast cancer without the use of a contrast agent . High b‐value (>1000 s/mm 2 ) DWI has its strength in lesion detection and characterization by maximizing tissue contrast between diseased and normal tissue.…”
mentioning
confidence: 99%